(untitled) (ENTHYMEMA, 2014)
This is the revised transcript of a conversation between Darko Suvin [DS] and Federico Pianzola [FP]. The topics discussed are many and the focus keeps zooming back and forth from the historical context of humanities vs. resurgent fascism to formal remarks on literature, theatre, utopia, narrative, and other themes. Particular emphasis is given to a reflection on the dialectical and constructivist approach deployed by Suvin in his works.